Evaluation of indented prestressing wires for KDOT bridge members - Bogner, Derek M. (Kansas State University, 2023)
This paper presents the evaluation of indented prestressing wires for Kansas Department of Transportation’s (KDOT) bridge members. This evaluation contains the review of KDOT’s current design practice with prestressed concrete members, the development of alternate member designs utilizing indented prestressing wires, the development of a test plan, the determination of the transfer lengths, loading the specimens to failure, and analysis of the data collected. This purpose of this research was to investigate opportunities to utilize indented prestressing wires in KDOT bridge members to optimize designs to be more efficient while upholding safety standards. Due to the proven shorter development lengths of indented wires in comparison to 7-wire strands of similar sizes, the member selected that had the highest opportunity to showcase the advantages of this was the prestressed deck panel. For this research, six prestressed panels were created using three differing prestressing tendons: 3/8” 7-wire strand, 8 mm T4 European style indented wire, and an 8 mm T2 European style indented wire. Each prestressing tendon had two panels that were created, a 3” by 24” by 72” panel, and a 3” by 24” by 96” panel. After casting, the transfer lengths were determined and a 5 1/2” cast-in-place concrete topping was placed on top of the panels. The panels were then loaded to their ultimate experimental moment-carrying capacity using three-point loading. The data collected was then compared to each respective theoretical value, and to each other. The indented prestressing wires were stronger for the six-foot panel, while having a less area of steel and prestressing force. The 7-wire strand was stronger for the eight-foot panel, due to the wire being fully developed, with the indented prestressing wires being close behind. All panels broke above AASHTO strength recommendations, giving another viable prestressing tendon that KDOT can utilize in their prestressed deck panels.
Keywords: Indented wires; Prestressed concrete